How the social enterprise creates social value, in case of education - Uyanga.G; Odontamir.E, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Due to the legal and economic characteristics of the country, most of social enterprises are registered as not-for profit organizations, in Mongolia. Especially, for the emerging market economy, the role of social enterprises is utmost essential to fill the gap of social issues which could not solved immediately by the government and other parties. As for organizational level, the sustainability of social enterprises depends on how they deliver proper or value added products to their target market. The impact on social value will be appreciable, if they implement their activities successfully and reach the target population. Thus, this study was examined the social enterprises in the education sector of Mongolia, and explored the characteristics of their activities in the context of social innovation.